(untitled) (Global Journal of Science Frontier Research, 2013)
The object of the present paper is to derive the sufficient conditions for certain subclasses of -valent analytic functions in the open unit disk. A number of known results would follow upon specializing the parameters involved in our main results. Also, sufficient conditions are found for function to be univalent.